2018
DOI: 10.3389/fpsyg.2018.01000
|View full text |Cite
|
Sign up to set email alerts
|

Background Odors Modulate N170 ERP Component and Perception of Emotional Facial Stimuli

Abstract: Successful social interaction relies on the accurate decoding of other peoples’ emotional signals, and their contextual integration. However, little is known about how contextual odors may lead to modulation of cortical processing in response to facial expressions. We investigated how unpleasant and pleasant contextual background odors affected emotion perception and cortical event-related potential (ERP) responses to pictures of faces expressing happy, neutral and disgusted facial expressions. Faces were, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 55 publications
6
29
2
Order By: Relevance
“…Faces, independently of their expressions, were rated as more negative in the unpleasant odor condition and more positive in the pleasant odor condition, replicating results of previous studies (Cook et al, 2015;Cook et al, 2018;Syrjänen et al, 2018). Similar to previous research, faces were also rated as more arousing during odor exposure compared to the no-odor control condition (Cook et al, 2015;Syrjänen et al, 2018). Manipulation checks confirmed that the ratings of odor valence and intensity confirmed our expectations.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Faces, independently of their expressions, were rated as more negative in the unpleasant odor condition and more positive in the pleasant odor condition, replicating results of previous studies (Cook et al, 2015;Cook et al, 2018;Syrjänen et al, 2018). Similar to previous research, faces were also rated as more arousing during odor exposure compared to the no-odor control condition (Cook et al, 2015;Syrjänen et al, 2018). Manipulation checks confirmed that the ratings of odor valence and intensity confirmed our expectations.…”
Section: Discussionsupporting
confidence: 87%
“…Cook et al (2017) showed that the rated valence of faces is affected by congruent odors; disgusted faces were rated as more negative in an unpleasant odor context and happy faces were rated as more positive in a pleasant odor context. However, this specific interaction has not been found in other studies (Cook et al, 2015;Cook et al, 2018;Syrjänen et al, 2018). In general, results indicate that affective odors affect valence ratings of faces regardless of their expression (e.g.…”
Section: Introductioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Odors can modulate the recognition of disgust (Seubert et al, 2010), or happiness (Leppänen & Hietanen, 2003), while in the ambient odor conditions Reaction Times (RTs) in simple visual or auditory tasks significantly decrease (Millot, Brand, & Morand, 2002). Background odors may modulate the perception of emotional facial stimuli (Syrjänen et al, 2018) or attention may be modulated due to the effects of ambient odors (Michael et., 2003;Seigneuric et al, 2010). This indicates that olfactory stimuli may affect the modalities of perception and attention.…”
mentioning
confidence: 99%